Healthy learning mind - Effectiveness of a mindfulness program on mental health compared to a relaxation program and teaching as usual in schools: A cluster-randomised controlled trial - S.-M. Volanen; M. Lassander; N. Hankonen; P. Santalahti; M. Hintsanen; N. Simonsen; A. Raevuori; S. Mullola; T. Vahlberg; A. But; S. Suominen (Elsevier, 2025)
A short 9-week MBI in school-setting provides slight benefits over a relaxation program and teaching as usual. Future research should investigate whether embedding regular mindfulness-based practice in curriculums could intensify the effects.\nMindfulness-Based Interventions (MBIs) have shown promising effects on mental health among children and adolescents, but high-quality studies examining the topic are lacking. The present study assessed the effects of MBI on mental health in school-setting in an extensive randomised controlled trial.\nFinnish school children and adolescents (N = 3519), aged 12-15 years (6th to 8th graders), from 56 schools were randomized into a 9 week MBI group, and control groups with a relaxation program or teaching as usual. The primary outcomes were resilience, socio-emotional functioning, and depressive symptoms at baseline, at completion of the programs at 9 weeks (T9), and at follow-up at 26 weeks (T26).\nOverall, mindfulness did not show more beneficial effects on the primary outcomes compared to the controls except for resilience for which a positive intervention effect was found at T9 in all participants (β=1.18, SE 0.57, p = 0.04) as compared to the relaxation group. In addition, in gender and grade related analyses, MBI lowered depressive symptoms in girls at T26 (β=-0.49, SE 0.21, p = 0.02) and improved socio-emotional functioning at T9 (β=-1.37, SE 0.69, p = 0.049) and at T26 (β=-1.71, SE 0.73, p = 0.02) among 7th graders as compared to relaxation.\nThe inactive control group was smaller than the intervention and active control groups, reducing statistical power.\nCONCLUSIONS\nBACKGROUND\nMETHODS\nRESULTS\nLIMITATIONS